How Counterpart Theory Saves Nonreductive Physicalism. Issue 509 (16th January 2018) - Tiehen, Justin
Abstract: Nonreductive physicalism faces serious problems regarding causal exclusion, causal heterogeneity, and the nature of realization. In this paper I advance solutions to each of those problems. The proposed solutions all depend crucially on embracing modal counterpart theory. Hence, the paper's thesis: counterpart theory saves nonreductive physicalism. I take as my inspiration the view that mental tokens are constituted by physical tokens in the same way statues are constituted by lumps of clay. I break from other philosophers who have pursued this line, however, in that I hold that constitution is identity. Much of the value of the comparison to statues and lumps is that it calls to mind the resources used to defend constitution-as-identity, most notably that of counterpart theory. Along the way, I discuss the virtues of a trope ontology, modal objections to token identity theories, the prospects of conditional analyses of causal powers, the subset account of realization, and the grounding problem. I also endorse a novel, empirical argument in favor of counterpart theory.